Investigation of a CDDW Hamiltonian to Explore Possibility of Magneto-Quantum Oscillations in Electronic Specific Heat of Hole-Doped Cuprates - Partha Goswami; Manju Rani (Advances in Condensed Matter Physics)
We investigate a chiral d-density wave (CDDW) mean field model Hamiltonian in the momentum space suitable for the hole-doped cuprates, such as YBCO, in the pseudogap phase to obtain the Fermi surface (FS) topologies, including the anisotropy parameter(́𝜀) and the elastic scattering by disorder potential (|𝑣0|). For ́𝜀=0, with the chemical potential 𝜇=−0.27 eV for 10% doping level and |𝑣0|≥|𝑡| (where |𝑡|=0.25 eV is the first neighbor hopping), at zero/non-zero magnetic field (𝐵), the FS on the first Brillouin zone is found to correspond to electron pockets around antinodal regions and barely visible patches around nodal regions. For ́𝜀≠0, we find Pomeranchuk distortion of FS. We next relate our findings regarding FS to the magneto-quantum oscillations in the electronic specific heat. Since the nodal quasiparticle energy values for 𝐵=0 are found to be greater than 𝜇 for |𝑣0|≥|𝑡|, the origin of the oscillations for nonzero 𝐵 corresponds to the Fermi pockets around antinodal regions. The oscillations are shown to take place in the weak disorder regime (|𝑣0|=0.25eV) only.